The Impact of diet on the digestive, cardiovascular and immune systems - Kobierecki, Mateusz; Kwaśniewska, Oliwia; Misiak, Jakub; Urbaś, Michał; Ojdana, Miłosz; Demianenko, Yehor; Czekaj, Oliwia; Kościołek, Aleksandra; Kościołek, Dawid; Kępczyk, Martyna (Journal of Education, Health and Sport, 2024)
INTRODUCTION AND AIM OF WORK One of the key factors shaping human health is diet. It serves as the foundation for the functioning of cells, organs, and the entire body. Properly chosen food has an impact, among other things, on the functioning of the immune, digestive, and cardiovascular systems. MATERIALS AND METHODS The objective of this study is to analyze the changes in the functioning of the cardiovascular, digestive, and immune systems through the application of different dietary approaches. For this purpose, an original questionnaire was developed. The questionnaire was distributed via social media (Telegram platform) in August 2023 among the population of Ukraine. RESULTS We collected a total of 94 surveys, with an average participant age of 26 years. A similar number of participants indicated consuming meals 3 times, 4 times, or 5 times a day. These were 23 individuals (24.47%), 25 individuals (26.6%), and 21 individuals (22.3%) respectively. The analysis of correlations revealed a negative correlation between the frequency of meal consumption and the frequency of infections (r = -0.21, p = 0.035). A significant relationship was also observed between body weight and the frequency of meal consumption (r = 0.34, p < 0.001). However, no significant relationship was found between following a special diet and body weight (p > 0.05). CONCLUSIONS The collected results suggest a connection between dietary habits and the frequency of infections as well as body weight. Interestingly, this relationship was related specifically to the frequency of meal consumption and was not linked to the intake of specific food groups. The obtained results highlight the significance of regular meal consumption in maintaining a healthy body weight and reducing the frequency of infections.